Odpowiedź :
a) 1,2x + 0,3 = 0,8x - 0,5
1,2x - 0,8x = -0,5 - 0,3
0,4x = -0,8
x= -0,8/0,4
x = -2
b) 3(x - 2) = 9x + 18
3x - 6 = 9x + 18
3x - 9x = 18 + 6
-6x = 24
x = 24/-6
x= -4
2. Rozwiąż równanie 4x − 4 = 3x + 5.
4x - 3x = 5 + 4
x = 9
3. Rozwiąż równania.
5x + 7 = 22
5x = 22 - 7
5x = 15
x = 15/5
x = 3
5x − 5 = x + 7
5x - x = 7 + 5
4x = 12
x = 12/4
x = 3
2(x + 4) = x − 7
2x + 8 = x - 7
2x - x = -7 - 8
x = -15
Odpowiedź:
a) 1,2x-0,8x = -0,3- 0,5
0,4x = -0,8/*2,5
x= - 2
b) 3x-6=9x+18
3x-9x=6+18
-6x = 24/:6
x = -4
2.
4x-3x=4+5
x=9
3.
a) 5x= -7+22
5x=15/:5
x=3
b) 5x-x = 5+7
4x=12/:4
x=3
c) 2x + 8 = x - 7
2x-x = -8-7
x = -15